The behavioural implications of women's empowerment programmes - Lata Gangadharan; Tarun Jain; Pushkar Maitra; Joseph Vecci (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2016)
Participatory community programmes are a potentially important tool for social empowerment and economic development. How do participatory programmes that specifically target women affect community trust and cohesion? This question is important since the longterm success of such programmes might depend critically on the behavioural transformation that they generate. We examine this question in the context of JEEViKA, a community-based empowerment programme that targets women in Bihar, India. Field experiments and surveys in 40 villages in Bihar reveal that JEEViKA is associated with significantly greater trust by and towards women suggesting an important role for community programmes in building economic relationships. We do not find significant differences between JEEViKA and non-JEEViKA villages in term of trustworthiness. Finally, we also find evidence that exposure to JEEViKA is associated with changes in attitudes towards women and their appropriate role in society.
Keywords: C93; D03; H43; H53; H75; J16; 330; community development programmes; women's empowerment; artefactual field experiments; trust; Bihar; India